PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH TSANAWIYAH NEGERI 2 BANDAR LAMPUNG - Devi Sela Eka Selvia; Syamsuri Ali; Ayu Anggraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Two Stay Two Stray (TSTS) learning model on the learning outcomes of Akidah Akhlak among eighth-grade students at MTs Negeri 2 Bandar Lampung. This quantitative research used an ex post facto design with a sample of 70 students selected through simple random sampling. Data were collected using questionnaires and documentation, and analyzed using simple linear regression.The results show that the TSTS learning model has a positive and significant effect on learning outcomes, with t-count (15.519) > t-table (1.994) and significance value 0.000 < 0.05. The coefficient of determination (R²) of 0.780 indicates that 78% of learning outcomes are influenced by the TSTS model. Additionally, the number of students who did not meet the Minimum Mastery Criteria decreased from 20 to 9 students.In conclusion, the implementation of the TSTS model improves students’ learning outcomes.